Policy Implementation of Educational Quality Improvement Based on National Education Standard - Lydia, Lydia; Fitria, Happy; Puspita, Yenny (Journal of Social Work and Science Education, 2020)
The objective of the study was to know the implementation of policies to improve the quality of education at SMP Negeri 2 Sekayu towards the National Education Standards. This study uses a qualitative method. Subjects in this study were school principals, Deputy for Facilities and Infrastructure, Student Associates, Teachers, and Students. Data collection was carried out by interview, observation, and documentation. Data were analyzed by data reduction, data presentation, and conculsion drawing. From the research results it can be concluded that the quality of education at SMP Negeri 2 Sekayu has met the requirements as a school with very good quality with the accreditation it has, namely the predicate "A" as a pilot school in Musi Banyuasin Regency. The National Education Standards that are applied are guided by the regulations issued by the Directorate General of Primary and Secondary Education, Ministry of Education and Culture in 2017 including, graduate competency standards, process standards, content standards, assessment standards, education and educational staff standards, facilities and infrastructure standards, standards management and financing standards have been implemented properly.